2020
DOI: 10.1088/1755-1315/460/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Gracilaria sp. as single-or co-digestion feedstock for biogas production

Abstract: High consumption of fossil fuels in Indonesia needs to be reduced by using renewable energy, such as from biomass. In Indonesia, as one of the largest maritime countries, macroalgae (i.e. seaweed) are also considered as potential renewable biomass feedstocks for substituting any land biomass. This study aimed to investigate biodegradability and biogas potential of macroalgae (Gracilaria sp.) as single-or co-digestion feedstock using anaerobic digestion technology. The biochemical methane potential (BMP) test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…A high TS concentration resulted in a reduction in hydrolysis rate and an inhibition in methanogenesis due to mass transfers limitations. A previous study also found that an increase in MC values has correlation to an increase in SMP values, and vice versa [48].…”
Section: The Effect Of Co-digestion Of Wgv With Td At Different Ratio...mentioning
confidence: 81%
See 4 more Smart Citations
“…A high TS concentration resulted in a reduction in hydrolysis rate and an inhibition in methanogenesis due to mass transfers limitations. A previous study also found that an increase in MC values has correlation to an increase in SMP values, and vice versa [48].…”
Section: The Effect Of Co-digestion Of Wgv With Td At Different Ratio...mentioning
confidence: 81%
“…Control positive used in this study was α-cellulose powder C8002 (Sigma Alrdrich, Singapore). Control inoculum was prepared using digestate from a full-scale digester treating cattle manure at Balai Besar Pelatihan Peternakan in Batu City, which operated under mesophilic condition, as previously used in our previous studies [12,48,57,58]. The digestate was sieved using a 1 mm screen for removing larger particles, then it was deggased for 48 hours at 37 o C to eliminate the residual biogas.…”
Section: Feedstocks Control Positive and Inoculumsmentioning
confidence: 99%
See 3 more Smart Citations